Exploring Green Information Technology Implementation in Collaborative Enterprise - Anthony, Bokolo Jnr.; Mazlina, Abdul Majid; Awanis, Romli (American Scientific Publisher, 2018)
The rapid increase of Collaborative Enterprises (CE) such as organizations and various institutions reflects the growing number of foreign and local investors initiating domestic based enterprises all over the world. Consequently, sustainability in CE calls the organizations management to promote Green Information Technology (IT) initiatives that can decrease water, cost and energy consumptions while having negligible carbon footprint. Green IT towards energy efficient aims to support CE deploy better lighting, operational temperature control, better indoor air and ventilation which contribute to healthy working environments by decreasing dangerous air pollutants that may result to respiratory disease within enterprise buildings. However in implementing Green IT initiatives in CE, comprehensive strategies should also be put in place to change the managerial and administrative mind-sets of organizations management and more specifically staffs and practitioners towards ensuring that they support Green IT. CE needs to be aware of the dimensions to be considered by staffs and practitioners in implementing Green IT initiatives. Therefore this paper explores existing studies on Green IT to identify the dimensions of Green IT implementation in CE by utilizing secondary data synthesized and extracted from previous studies. Based on the dimension a multi-dimensional model is designed and explored using survey data collected from 133 respondents from various collaborative enterprises across Malaysia. Findings from the survey shows that all dimensions in the model were important and are to be considered in implementing Green IT initiatives in collaborative enterprises.